Evaluación de amenaza por deslizamiento para rellenos antrópicos en la ciudad de Manizales- Colombia (2019)
In the past years, the landslides have been caused the natural threat as a greatest damage, victims and loss of human life in Manizales; after rains in the city for many days in a row or due to the occurrence of high intensity rains in a very short period of time. Due to the fact there are riverbed fillings in the city were built in the 60s and 80s, on which neighborhoods are currently settled, twelve were located on the northern slope of the Chinchiná river; the present study was conducted with the purpose of evaluating the landslide threat condition presented by these fills, considering the factors that detonating precipitation and earthquakes. Manizales Municipality has the 2017-2031 territorial Arrangement Planning (TAP), in which a landslide threat map is exposed by the urban area of the city. But, consulting different sources, no specific studies were found evaluating the landslide threat for anthropogenic landfills in the city; this is why this study arises. It should be noted the development of this thesis began before the preparation of the current (TAP) for the city. Twelve anthropic riverbed fillings were located on the northern slope of Chinchiná River; the geometries were elaborated, based on cartography of the 60s and 2004 obtained from plates from the Geographical Institute Agustín Codazzi (IGAC). These fillings are made up of two stratums, anthropic materials and the Casabianca Formation, to which their physical, mechanical and hydraulic properties were assigned to characterize them. Based on the historical rainfall records of the El Carmen, Hospital and Agronomy rainfall stations, intensity values (mm / day) were projected and calculated for return periods (Tr) of 2.33, 10, 50, 100, 250 years. These values were used to define the infiltration rate, which would be entered into each of the landfills as a detonating for rain. The calculation of this infiltration rate (mm / day) shown in section 4.5.1. The detonating earthquake was included in the stability analysis of the 12 fills, as a peak seismic acceleration for certain return periods, Tr: 31 years, 225 years and 475 years. Later, 720 analysis scenarios were generated, 60 per fill, resulting from the different combinations of return periods Tr of the earthquake and rain detonating and mechanical properties of the fill stratum. Next, the stability analysis of each scenario was run using the slide software, to know the value of the safety factor SF of each filling. Knowing the result of the safety factor (SF) of each scenario per fill, the probability of failure was calculated and the landslide threat assessment was performed. This analysis considered the uncertainty in the parameters of soil resistance, cohesion and friction angle of the anthropic fill stratum, and the probability of occurrence of the detonating factors, rain and earthquake. The objective of this thesis was to establish the level of landslide threat for anthropic fills in Manizales-Colombia, however considering the results obtained, despite obtaining the probability of failure, it was not possible to generate threat curves, given that the results showed that the probability of failure of the 12 fillings studied was zero or too close to zero. Their probabilities of total failure were less than 0.0016.